(3GdSff GdcHjQs - (3CHh HcQ CMeO Hf GdMSjf Hf Ydj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s ((3eMehO Hf eMeO Hf EHQGgje GdMSjfi s)
(3ChdgG (B:s
(3hCeG RgQI aEfg cGf CNkG dbUi Hf cdGH , hef ChdGOg ef GdYTQI c YHO GdQMef Hf Yha hSYO GHf CHj hbGU s
(3BNQgG (B:s
(3HGH fabI GdCHhjf s
(3HBNQgG NW GHf GdUdGM SfI (B633 (3g` HUMI SeGY GdYdeGA Ydjg hgPg GdSeGYGJ gi GdJi JbOeJ ai GdCLRGA GdSGHbIs
(3HGdhQbI GdChdi NW eLO GdOjf GdajQhRCHGOi UGMH GdbGehS GdeMjWs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
Keywords: (3GdMOjK h GdeUWdMs